ศักยภาพของรายการ "ชุมชนนิมนต์ยิ้ม" ในการถ่ายทอดธรรมะให้กับเด็ก - ธีรติ ถนัดรบ (จุฬาลงกรณ์มหาวิทยาลัย, 2012)
This qualitative research aims at analyzing 1) the technique of dharma teaching through television animation "Chumchon Nimonyim", 2) the program’s attributes in that appeal and attractive to child viewers, 3) viewers’ understanding on dharma teaching. The research methods include 1) Textual Analysis television animation "Chumchon Nimonyim", 2) In-depth Interview on the program’s producer and program’s consultant, 3) Focus group Interview with the primary school students. The research finds that the studied program employs 2 techniques of presentation to teach dharma including story based and dharma topic based. In addition, there are 3 attributes in that appeal and attractive to child viewers. They are 1) entertaining quality by the animation’s format of presentation, 2) easily understanding from story-telling and dialogues in daily life, 3) having valued as a good content animation. For understanding dharma teaching, different ages of viewers have different learning abilities. The primary students (grade 1-3) learn and understand dharma teaching in the program less than the upper primary students (grade 4-6). As a result of complicated story with many sub plots, children interpretations of dharma tend to be mislead. Concerning with the narrative structure, if dharma is less emphasized than surrounding story, children may perceive that highlight story as the main theme.